Pengaruh Tingkat Bunga Diskrit dan Jangka Waktu Pinjaman terhadap Skema Amortisasi dan Total Biaya Pelunasan Utang - Ndruru, Albert Servant; Simangusong, Enjelita; Simanjuntak, Ferdyanto Abangan; Harefa, Alfon Brian (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study analyzes the effect of discrete interest rates and loan terms on the amortization scheme and total debt repayment costs. Debt amortization is a method of paying off loans periodically consisting of principal and interest. Variations in interest rates and loan terms can affect the amount of installments, the proportion of interest payments to principal, and the total costs that must be paid by the borrower. Using a quantitative approach and numerical simulation, this study evaluates the relationship between these variables to understand their impact on the debt repayment structure. The results show that higher interest rates increase total interest expenses, while longer loan terms can reduce monthly installments but increase total repayment costs due to interest accumulation. These findings are expected to help financial institutions in formulating optimal credit policies and provide guidance for borrowers in choosing the most efficient loan scheme.